The Innovation Elements Of Homestay Programmes On The East Coast Of Malaysia - Nor Syuhada Zulkefli; Zaimatul Awang; Suhaida Herni Suffarruddin (University of Primorska, Faculty of Tourism Studies, 2024)
Academica Turistica - Tourism and Innovation Journal, Volume 16 Issue 2 Page (233-246)